International Night: A presentation of cultural & traditional event - UMP, PNC
In conjunction with its Academic Carnival and ExpoConvo’09, University Malaysia Pahang (UMP) held an “International Night” on September 30 last year, to encourage positive manifestation of the various cultures and traditions of the university’s 150 international students.